Dorsal-Ventral Differences in Retinal Structure in the Pigmented Royal College of Surgeons Model of Retinal Degeneration - Greferath, Una; Huynh, Mario; Jobling, Andrew Ian; Vessey, Kirstan Anne; Venables, Gene; Surrao, Denver; O'Neill, Helen Christine; Limnios, Ioannis J.; Fletcher, Erica Lucy (Frontiers in Cellular Neuroscience, 2021)
Retinitis pigmentosa is a family of inherited retinal degenerations associated with gradual loss of photoreceptors, that ultimately leads to irreversible vision loss. The Royal College of Surgeon’s (RCS) rat carries a recessive mutation affecting mer proto-oncogene tyrosine kinase (merTK), that models autosomal recessive disease. The aim of this study was to understand the glial, microglial and photoreceptor changes that occur in different retinal locations with advancing disease. Pigmented RCS rats (RCS-p+/LAV) and age-matched isogenic control RDY (RCS-rdy +p+/LAV) rats aged postnatal day 18 to 6 months were evaluated for in vivo retinal structure and function using optical coherence tomography and electroretinography. Retinal tissues were assessed using high resolution immunocytochemistry to evaluate changes in photoreceptors, glia and microglia in the dorsal and ventral retina. Photoreceptor dysfunction and death occurred from one month of age. There was a striking difference in loss of photoreceptors between the dorsal and ventral retina, with a greater number of photoreceptors surviving in the dorsal retina, despite being adjacent a layer of photoreceptor debris within the subretinal space. Loss of photoreceptors in the ventral retina was associated with fragmentation of the outer limiting membrane, extension of glial processes into the subretinal space that was accompanied by possible adhesion and migration of mononuclear phagocytes in the subretinal space. Overall, these findings highlight that breakdown of the outer limiting membrane could play an important role in exacerbating photoreceptor loss in the ventral retina. Our results also highlight the value of using the RCS rat to model sectorial retinitis pigmentosa, a disease known to predominantly effect the inferior retina.